Enacting a pedagogy of reflection in initial teacher education using critical incident identification and examination: a self-study of practice. Issue 1 (2nd January 2021) - Brandenburg, Robyn
ABSTRACT: This article examines what it means for a teacher educator to enact a pedagogy of reflective practice in an initial teacher education classroom using self-study methodology. The focus of the article is the examination of a critical interaction that occurred in a third-year Bachelor of Education mathematics education tutorial ( N = 15). The critical incident prompted further reflection through collecting and analysing data that included pre-service teacher (PST) oral feedback during the tutorial; structured written feedback that was based on peer presentations during tutorials; and mid-semester and post-semester 'freewrites'. Teacher educator journal reflections provided further data for analysis. Thematic analysis together with teacher educator critical incident analysis, revealed key understandings for both the PSTs and the teacher educator. These learning outcomes included the importance of identifying PST perceptions and practices associated with participating in peer assessment; the incongruities between oral and written feedback; the crucial need for PST scaffolding when providing feedback; the impact of the learning environment; and the role of the teacher educator in explicitly facilitating discussions associated with critical incidents, conversations and interactions. Using self-study methodology to examine teaching surfaced unspoken and assumed beliefs, and through examination, led to authentic, negotiated learning and improved outcomes for PSTs and teacher educators.